LAS ANCIANAS MAYAS PREHISPÁNICAS EN LA ICONOGRAFÍA Y LAS FUENTES COLONIALES - García Valgañón, Rocío (Studia Europaea Gnesnensia, 2017)
The paper offers a revision of the current knowledge concerning elderly Maya women, based on Maya and Spanish colonial sources, as well as iconographic artefacts such as vessels, figurines and mural painting. The main objective is to determine whether information derived from the above sources is congruent and whether it coincides with the current notions about these women. Moreover, special attention is paid to certain roles played by the elderly Maya women, which distinguish them from other female members of the community and, at the same time, bring them almost on a par with men.